Звонок для учителя, или Лес рук: [сборник] / Н. Абгарян, А. Цыпкин и К° - Абгарян Наринэ (#школьноприкольно, 2021)
Экземпляры: (20211110) / Инвентарный номер: 61880 / Цена: 260.27 / Сис.шифр: Р2ср / Авт.знак: А 13 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6